ERGONOMIC ANALYSIS OF THE ANOA 2 6X6 PANZER STEERING ROOM USING NORDIC BODY MAP - Hardy Adiluhung; I Made Gede Arimbawa; Ida Ayu Dyah Maharani (International Journal of Social Science, 2025)
Comfort and safety in the driver's seat of a military vehicle are crucial aspects in supporting operational effectiveness. The Anoa 2 6x6 Panzer is a combat vehicle used by the Indonesian National Army (TNI) with its main function as an armored personnel carrier. However, several studies show that ergonomic aspects in wheelhouse design still need to be optimized to reduce the risk of musculoskeletal disorders (Musculoskeletal Disorders/MSDs) on the driver. This study uses the Nordic Body Map (NBM) method to evaluate the comfort level and potential risk of injury due to the driver's working posture during vehicle operation. Data was collected through questionnaires filled out by 21 Anoa 2 6x6 Panzer drivers who were actively on duty in the field. The research results show that the lower back, shoulders, neck and wrist areas are the parts of the body that experience the most complaints due to less ergonomic chair design, pedal position and control layout. Based on these results, recommendations for a more ergonomic design were prepared to reduce the driver's physical workload and increase comfort in operating the Anoa 2 6x6 Panzer